Uniform droplet splitting and detection using Lab-on-Chip flow cytometry on a microfluidic PDMS device - Kunstmann-Olsen, Casper; Hanczyc, Martin M.; Hoyland, James; Rasmussen, Steen; Rubahn, Horst-Günter (Sensors and actuators. B, Chemical, 2016)
A PDMS chip is fabricated using soft lithography and applied to investigate the formation and division of nitrobenzene (NB) droplets in a two-phase system stabilized by oleic acid. Using an integrated on-chip flow cytometer setup, effected with optical fibers, droplet size distributions are analyzed in situ based on optical signal intensities. By controlling the hydrodynamic flow focusing, uniform droplets of sizes between 100μm and 300μm are created with precise size control. Cross-flow shearing allows one to divide these droplets into anything from 2 to 9 individual droplets, depending on flow parameters.